The Role of Goan Folklore In Cultural Tourism: Shaping Tourist Experiences And Preserving Community Identity - Barreto, Nigel; Da Costa Frias, Nafisa (International Journal of Scientific Research and Management (IJSRM), 2025)
Cultural tourism is a new element of tourism experiences and is becoming more relevant, especially when tourists are increasingly interested in authentic, experiential cultural activities. The research explores the growth in the importance of cultural tourism in Goa and particularly in the role that folklore and traditions play in forming tourists' experiences. The goals of the research are the identification of factors that can affect participation in folklore-related activities by tourists and tourists' perceptions of authenticity. A survey involving 350 tourists visiting diverse cultural sites of Goa had structured questionnaires for gathering data. This study revealed cultural satisfaction, perceived authenticity, and cultural immersion as great predictors of folklore activity participation and thus, the imperative need to retain local tradition with authentic culture for engagement enhancement..